Paths taken by the category "Traditional Block of Maranhão" in the Ludovicense carnival - Neto, Euclides Moreira (Seven Editora, 2024)
This article presents a narrative that describes how the groups of Traditional Blocks of Maranhão (BTMs) emerged on the island of São Luís, which currently covers four municipalities, an area considered the metropolitan region of the capital of Maranhão. An attempt is made to conceptualize this cultural manifestation of the carnival cycle, presenting how it was hybridized and naturalized by the urban and peripheral people of the region, as it arose among the rich and wealthy families of the city. From this perspective, concepts of popular culture, tradition and how the cultural groups of the carnival field were adapted are discussed. DOI:https://doi.org/10.56238/sevened2024.007-091